2011
DOI: 10.1111/j.1365-2702.2010.03637.x
|View full text |Cite
|
Sign up to set email alerts
|

Placement Development Teams and interprofessional education with healthcare students

Abstract: To embed interprofessional education in practice-based professions' curricula and clinical placements requires active, supportive structures and local facilitation. Structures such as Placement Development Teams can help to achieve this where organisational cultures are influenced by committed staff. Students require persuasion concerning the benefits of interprofessional education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…A total of 41 studies were included in the final synthesis . Study characteristics are summarised in Tables .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 41 studies were included in the final synthesis . Study characteristics are summarised in Tables .…”
Section: Resultsmentioning
confidence: 99%
“…This engagement would ensure widespread support provision for greater numbers of students across the professions and sector. (Placement development team members, varied placement sites)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The students’ reasoning on this point is supported by Nikendei et al [34] and Williamson et al . [35] who concluded that ward rounds training was urgently required. Nørgaard et al .…”
Section: Discussionmentioning
confidence: 99%
“…Practice-based, rather than classroom-based, collaborative learning has been commended as an effective application of IPL. [2][3][4][5][6][7] However, it can be cumbersome to arrange and supervise. 8 In rural Australia with its relative workforce shortage, sustainable, practice-based IPL can be particularly challenging.…”
Section: Introductionmentioning
confidence: 99%